Ferroelectric artificial synapse for neuromorphic computing and flexible applications - Li, Qing-Xuan; Liu, Yi-Lun; Cao, Yuan-Yuan; Wang, Tian-Yu; Zhu, Hao; Ji, Li; Liu, Wen-Jun; Sun, Qing-Qing; Zhang, David Wei; Chen, Lin (Fundamental research (Beijing), 2023)
Research of artificial synapses is increasing in popularity with the development of bioelectronics and the appearance of wearable devices. Because the high-temperature treatment process of inorganic materials is not compatible with flexible substrates, organic ferroelectric materials that are easier to process have emerged as alternatives. An organic synaptic device based on P(VDF-TrFE) was prepared in this study. The device showed reliable P/E endurance over 104 cycles and a data storage retention capability at 80 °C over 104 s. Simultaneously, it possessed excellent synaptic functions, including short-term/ long-term synaptic plasticity and spike-timing-dependent plasticity. In addition, the ferroelectric performance of the device remained stable even under bending (7 mm bending radius) or after 500 bending cycles. This work shows that low-temperature processed organic ferroelectric materials can provide new ideas for the future development of wearable electronics and flexible artificial synapses. [Display omitted]